Drug release study of the chitosan-based nanoparticles - Yedi Herdiana; Nasrul Wathoni; Shaharum Shamsuddin; Muchtaridi Muchtaridi (Heliyon, 2022)
Recently, multifunctional drug delivery systems (DDSs) have been designed to provide a comprehensive approach with multiple functionalities, including diagnostic imaging, targeted drug delivery, and controlled drug release. Chitosan-based drug nanoparticles (CSNPs) systems are employed as diagnostic imaging and delivering the drug to particular targeted sites in a regulated manner. Drug release is an important factor in ensuring high reproducibility, stability, quality control of CSNPs, and scientific-based for developing CSNPs. Several factors influence drug release from CSNPs, including composition, composition ratio, ingredient interactions, and preparation methods. Early, CSNPs were used for improving drug solubility, stability, pharmacokinetics, and pharmacotherapeutics properties. Chitosan has been developed toward a multifunctional drug delivery system by exploring positively charged properties and modifiable functional groups. Various modifications to the polymer backbone, charge, or functional groups will undoubtedly affect the drug release from CSNPs. The drug release from CSNPs has a significant influence on its therapeutic actions. Our review's objective was to summarize and discuss the relationship between the modification in CSNPs as multifunctional delivery systems and drug release properties and kinetics of the drug release model. Kinetic models help describe the release rate, leading to increased efficiency, accuracy, the safety of the dose, optimizing the drug delivery device's design, evaluating the drug release rate, and improvement of patient compatibility. In conclusion, almost all CSNPs showed bi-phasic release, initial burst release drug in a particular time followed controlled manner release in achieving the expected release, stimuli external can be applied. CSNPs are a promising technique for multifunctional drug delivery systems.